MODELING OF THE PROVIDED CONFIGURATION OF THE MAGNETIC FIELD IN THE PLASMA CLOUD - G. A. Mankaeva; L. N. Dzhimbeeva; B. B. Mikhalyaev; S. B. Derteev; I. A. Lagaev (Современная наука и инновации, 2022)
In recent years researches of the dynamics of magnetic clouds have accumulated a wealth of data on their behavior under the action of magnetic fields. In the case of researching coronal mass ejections, the problem lies in setting boundary and initial conditions for magnetic fields and other physical parameters: temperature, velocity, pressure, etc.